Completing the progression establishing an international baseline of primary, middle and secondary students' views of scientific inquiry - Lederman, Judith S.; Bartels, Selina; Jimenez, Juan; Lederman, Norman G.; Acosta, Katherine; Adbo, Karina; Akerson, Valarie L.; de Andrade, Mariana a. Bologna Soares; Avraamidou, Lucy; Barber, Kerry-Anne; Blanquet, Estelle; Boujaoude, Saouma; et al. (International Journal of Science Education, 2024)
Knowledge of scientific inquiry (SI) is considered essential to the development of an individual's Scientific Literacy (SL) and therefore, SI is included in many international science education reform documents. Two previous large scale international studies assessed the SI understandings of students entering middle school and secondary students at the end of their formal K-12 science education. The purpose of this international project was to use the VASI-E to collect data on what primary level students have learned about SI in their first few years of school. This study adds to previous research to bridge the landscape of SI understandings now with representation from primary, middle and high school samples. A total of 4,238 students from 35 countries/regions spanning six continents participated in the study. The results show that globally, primary students are not adequately informed about SI for their age group. However, when compared with the students in the previous international studies (grades seven and 12), the primary students' understandings were surprisingly closer to the levels of understanding of SI of the secondary school students than those in the seventh grade study.